Web-spinning heroics critical essays on the history and meaning of Spider-Man - Peaslee, Robert Moses, 1973-; Weiner, Robert G., 1966- (McFarland & Co., Publishers, 2012)
"This volume traverses boundaries of medium, genre, epistemology, and discipline in insightful, passionate essays that move forward the study of one of the world's most beloved characters. The book is crafted for fans, creators, and academics alike. Foreword by Tom DeFalco, with poetry and afterword by Gary Jackson (winner of the 2009 Cave Canem Poetry Prize)"--Provided by publisher.